A Comprehensive Study of Artificial Intelligence and Machine Learning Approaches in Confronting the Coronavirus (COVID-19) Pandemic - Rahman M.M.; Khatun F.; Uzzaman A.; Sami S.I.; Bhuiyan M.A.-A.; Kiong T.S. (SAGE Publications Inc., 2023)
artificial intelligence; COVID-19; detection method; health care; health services; machine learning; supervised learning; Coronavirus; artificial intelligence; human; machine learning; pandemic; Artificial Intelligence; COVID-19; Humans; Machine Learning; Pandemics; SARS-CoV-2